Slow Approval Process of the Due Diligence Directive and the Different Paths for the Involvement of Trade Unions - Costantino Cordella (Italian Labour Law e-Journal, 2023)
In this article, we highlight the different positions expressed by the European Parliament and the European Commission on the need to provide for the involvement of trade unions in the new directive on Company Due Diligence. The Parliament's position tends to emphasize the importance of prior consultation with trade unions. In the opposite direction, the European Commission's draft directive, from a management perspective, understands due diligence compliance as a governance constraint decided unilaterally by companies. Considering these processes, we try to ask whether trade unions can autonomously contribute to the ecological transition of companies and the protection of human rights, considering the advantages and disadvantages of their involvement.